Promoting Transparency and Integrity Through the Disclosure of Financial Interests in Jordan - Nasrawin, Laith K. (Journal of Posthumanism, 2025)
The purpose of this article is to explore the statutory standards for disclosing financial interests for public offices as provided in the Jordanian Illicit Enrichment Law of 2014. The IE law establishes a specific department for disclosure of interests under the administration of the Ministry of Justice, which is responsible for receiving financial disclosure statements from persons subject to the law. It also sets criminal penalties on anyone who violates the regulations for disclosing the financial interests of assigned persons, their wives, and minors, as well as anyone who willfully provides erroneous data in personal statements provided by them. Despite the existence of a clear mechanism that works to ensure transparency and integrity in public life through the system of disclosing financial interests, these rules have not been efficiently implemented, and the number of individuals prosecuted for breaking the law has been minimal. As a result, the purpose of this study is to uncover flaws in the system of revealing financial interests, taking into account the organization of the department in question as well as the procedures for submitting financial interest declarations by holders of public office, their spouses, and minors.